Rancang Bangun Alat Tes Busi Motor Di Bengkel Motor - Jamaaluddin, Jamaaluddin; Wakhidian, Viete (Universitas Hang Tuah, 2019)
The ignitionsystemisanelectricalsystemonthe motor thatproducessparks inthe combustionchamber,theIgnitioncoilthatgenerateshighvoltage willgeneratesparkplugs andproducesparksonbothendsofthesparkplugelectrode.Theperfectionofthecombustion processgreatly affectsthemotorworksystem. Sparkplugconditionsmustbeinanoptimal state inorder toprovideagoodcontributiontomotor performance.Giventheelectronics systeminthemotorignitionsystemÂ canbeausefultoolfor Â analyzingsparks.Astable MultivibratorelectronicscircuitusingtheICNE555isusedasasignalgeneratorPWM(Pulse WidthModulation),whichwillservetheinputCDI asasubstituteforpulsermagnet,sothat theelectricalsystem can workwithoutusingmechanicsandcanbeutilizedasatooltobeable toanalyzetheperformanceofsparkplug motorcycle.Becausethesparkplug motorisoneof the main components that playan importantrolein theperformanceof motor fuel.